Ex Vivo Expansion of Human Mesenchymal Stem Cells in Defined Serum-Free Media - Sunghoon Jung; Krishna M. Panchalingam; Lawrence Rosenberg; Leo A. Behie (Stem Cells International)
Human mesenchymal stem cells (hMSCs) are presently being evaluated for their therapeutic potential in clinical studies to treat various diseases, disorders, and injuries. To date, early-phase studies have indicated that the use of both autologous and allogeneic hMSCs appear to be safe; however, efficacy has not been demonstrated in recent late-stage clinical trials. Optimized cell bioprocessing protocols may enhance the efficacy as well as safety of hMSC therapeutics. Classical media used for generating hMSCs are typically supplemented with ill-defined supplements such as fetal bovine serum (FBS) or human-sourced alternatives. Ideally, culture media are desired to have well-defined serum-free formulations that support the efficient production of hMSCs while maintaining their therapeutic and differentiation capacity. Towards this objective, we review here current cell culture media for hMSCs and discuss medium development strategies.